CRAVING FOR BALANCE IN KAMALA DAS'S POETRY: A FEMINIST PERSPECTIVE - Lovely, . (INTI International University, 2023)
This research delves into the exploration of balance in Kamala Das's poetry from a feminist standpoint. Das, a renowned Indian poet, articulates a compelling narrative of female experiences, reflecting societal imbalances. This study employs a feminist lens to scrutinize Das's verses, unraveling intricate threads of desire, societal expectations, and personal autonomy. By examining the poetic nuances, we decipher the complexities of Das's quest for equilibrium amid patriarchal constraints. The analysis underscores how Das's poetic expressions challenge traditional gender norms, offering a unique perspective on the persistent struggle for balance in a society laden with gender biases. This research contributes to the broader discourse on feminist literary criticism and South Asian women's writing.